Пиридил-2-, 1-окси-пиридил-2- и пиримидинил-2-трифторсульфураны - Пашинник, В.Е.; Козел, В.Н.; Шермолович, Ю.Г. (Украинский химический журнал, 2011)
Получены пиридил-2-, 1-окси-пиридил-2- и пиримидинил-2-трифторсульфураны. Изучено их взаимодействие со спиртами. Установлены пути превращений фторангидридов пиридин-2- и пиримидин-2-сульфеновых кислот. Синтезовано піридил-2-, 1-оксипіридил-2- та піримідиніл-2-трифторосульфурани. Досліджено їх взаємодію зі спиртами. Встановлено шляхи перетворення фтороангідридів піридин-2- та піримідин-2-сульфенових кислот. Pyridyl-2-, l-oxypyridyI-2- and pyrimi-dinyl-2-sulfur trifluorides have been synthesized. Their reactions with alcohols have been investigated. The routes of transformations of pyridine-2- and pyrimidine-2-suIfenyl chlorides have been established.